Performance of Soil Borehole Thermal Energy Storage System under Different Natural and Engineered Subsurface Conditions - Pandey, Upasana (University of Waterloo, 2023)
Borehole thermal energy storage (BTES) system, a type of underground thermal energy storage (UTES) systems, is a promising technology for sustainable space heating. BTES stores thermal energy in subsurface media (rock or soil) using borehole heat exchangers (BHEs). BTES installed in soil are specifically known as soil borehole thermal energy storage (SBTES) system. In SBTES, a heat carrier fluid (HCF) collects thermal energy from various heat sources such as solar energy and industrial waste heat, circulating it through the BHEs. The heat from the BHEs is transferred to the surrounding soil and stored as thermal energy in the soil deposits, thereby increasing its temperature. Subsequently, the stored energy is extracted through BHEs for space heating applications. The ability to retain stored energy in soil deposits depends on subsurface thermal and hydraulic conditions. Previous studies have explored various subsurface conditions (saturated, unsaturated, and groundwater flow) to capture their influence on the thermal performance of SBTES system. While previous studies focused specifically on the role of soil thermal conductivity under saturated soil conditions, the influence of other soil properties, particularly under different SBTES design conditions, has not been systematically explored. In unsaturated subsurface conditions, studies have concentrated on assessing the thermal performance of SBTES systems under varying moisture content conditions, while considering different water retention parameters. However, the understanding of the role of soil porosity in the thermal performance of SBTES in unsaturated soil, particularly under long-term operation scenarios, is limited. Additionally, existing studies have predominantly examined homogeneous soil conditions and have not accounted for soil layering. Further, while some studies have explored the impact of seasonal climatic fluctuations, they have primarily focused on variations in seasonal surface temperatures alone. The effect of surface pressure variations induced by factors such as evapotranspiration, groundwater table fluctuations, and other climatic conditions has not been thoroughly investigated. Previous studies regarding groundwater flow consideration often assumed the groundwater table to be flush with the ground surface, with the BHEs completely submerged into the groundwater. However, when different groundwater table depths are considered, where the BHEs are partially submerged, these studies did not take into account the influence of flow velocity. Previous studies have established that the consideration of groundwater flow is important in the analysis and design of SBTES systems. However, there is no systematic study available that explores the SBTES performance for a wide range of flow velocities and for multiple groundwater table depths considered in conjunction. Additionally, in the presence of high velocity groundwater flow, it is commonly recommended to avoid installing SBTES at the location without proper engineering modifications. However, currently no strategies exist to effectively mitigate the adverse effects of groundwater flow on the thermal performance of SBTES systems. The aim of this study is to develop better understanding of the influence of different subsurface conditions on the thermal performance of SBTES system through rigorous numerical analysis. The analysis incorporates saturated, unsaturated, and groundwater flow conditions to capture their respective impacts. Initially, a simplified conduction-based model is used to investigate the influence of physical and thermal properties of soil under different BHE spacing and injection heat flux scenarios for saturated soil condition. Subsequently, for unsaturated soil conditions, a coupled heat and mass transfer based numerical model is used to investigate the thermal behavior of SBTES systems under various subsurface moisture conditions, encompassing fully dry, fully saturated, and varying moisture content scenarios with different depths of the saturated soil zone. Additionally, the study examines the impact of seasonal surface pressure variations on the thermal performance of the SBTES system in unsaturated soil. Further, the role of soil porosity under different soil stratifications and soil moisture conditions on the thermal performance of the SBTES system in unsaturated soil is investigated to augment the existing knowledge in this area. The effects of groundwater flow on the short- and long-term performances of SBTES systems under fixed- and variable-energy supply and demand conditions are studied for different groundwater velocities and different groundwater table depths. Numerical simulations of a SBTES system are performed for four groundwater table depths and with four groundwater velocities ranging from 0 m s−1 to 1 × 10−5 m s−1. The study aimed to highlight the importance of conducting long-term analyses and quantifies the adverse effects of groundwater flow on the thermal performance of SBTES. Finally, a design aid is proposed in the form of vertical barriers to be installed within the SBTES domain, aimed at mitigating thermal losses resulting from groundwater flow. A comprehensive study is conducted to provide recommendations regarding the suitable type of vertical barriers, their appropriate positioning with respect to SBTES domain, and the anticipated improvement in thermal performance of SBTES system upon integration with the vertical barrier as a design aid. A detailed analysis is conducted for small, medium, and large-scale SBTES domain to provide a suitable range of vertical barrier design components, refining the geometry of the vertical barrier to achieve optimal thermal performance.
Keywords: borehole thermal energy storage; unsaturated soil; shallow geothermal energy